Mucormycosis as a Rare Infection in Lower Limb Necrotizing Fasciitis: A Case Report - Abdessamad, Hilal; Mokhbat, Jacques (International Journal of Clinical Research, 2023)
Introduction: Necrotizing fasciitis is a severe, life-threatening infection that can be fatal and rapidly progressive. It is usually caused by polymicrobial infection, monomicrobial infection by group-B streptococci (GBS) or staphylococci, or by anaerobes like Clostridium difficile that presents as a gas gangrene or rarely by fungi. Fungal infections, though found in diabetic foot ulcers, remain extremely rare agents in necrotizing fasciitis, often causing severe morbidity and higher mortality than regular bacterial infections. Though severe, these infections are not often late to diagnose and very few reports exist citing their presence. With our case report, we present another rare manifestation of Mucormycosis in a foot wound. Case Report: We present a 57-year-old diabetic male patient who presented with a rapidly progressing very painful right foot ulcer, with high-grade fever and fatigue that did not respond to surgical intervention and treatment with broad-spectrum antibiotics. Mucormycosis species were identified in wound cultures. The patient then underwent an amputation and was treated with liposomal Amphotericin B. Conclusion: This report aims to further highlight that virulent fungal infections, especially mucormycosis, should be considered when suspecting or diagnosing necrotizing fasciitis. An extensive review of the literature with our newly added case would serve as an eye-opener on this pathogen in the setting of difficult-to-treat necrotizing fasciitis.